Abstract of Invited Speaker : Research Opportunities in Japanese Universities and Tips for Scientific Publications - Siti Machmudah (IPTEK Journal of Proceedings Series, 2015)
This article gives information for researcher to do research in Japanese Universities based on author’s experience and some literatures. Researchers may obtain research opportunities with Japanese Universities through postdoctoral fellowship program provided by Japanese Society for the Promotion of Science (JSPS). Other financial supports to make research collaboration with Japanese Universities may also be applied through JSPS program. In addition, author summarized tips for scientific publications  both  in  international  conferences  and journals. The tips may help researchers to write a scientific article to be published in an international journal